(untitled) (Proceedings OPTIMAL, 2025)
Poor dental and oral health is usually based on lack of knowledge. To improve knowledge, health information supported by media is needed. Leaflets have the advantage of being designed in such a way as to suit their targets and are practical because they reduce the need for taking notes, while booklets make it easier to understand, in the form of small books, containing short and clear messages. The purpose of this study was to determine the difference in knowledge of dental and oral hygiene between providing information using leaflet and booklet media to children in grades IV and V of SDN 03 Tumpuk Tangah, Sawahlunto City. The type of research used is an experiment with a pretest and posttest design. The population of this study was all students in grades IV and V of SDN 03 Tumpuk Tangah, Sawahlunto City, totaling 40 students. The sample in this study was 40 people, the sampling technique was saturated samples. The method of data collection was by filling out a pretest- posttest questionnaire about dental and oral hygiene. Data analysis used was univariate and bivariate analysis. The results of the study showed that students’ knowledge before being given information about dental and oral hygiene was 55.0% with sufficient criteria and after being given counseling using leaflet media increased to 80.0%. Students’ knowledge before being given counseling on dental and oral hygiene was 60.0% with insufficient criteria and after being given counseling using booklet media increased to 90.0%. The conclusion of this study is that counseling using leaflet and booklet media can both improve knowledge of dental and oral hygiene. It is recommended that respondents apply the methods of maintaining dental and oral hygiene that have been given in everyday life.